2020
DOI: 10.1007/s12471-020-01431-z
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in the Netherlands: current epidemiological profile and mortality

Abstract: Introduction Infective endocarditis (IE) is associated with a high in-hospital and long term mortality. Although progress has been made in diagnostic approach and management of IE, morbidity and mortality of IE remain high. In the latest European guidelines, the importance of the multi-modality imaging in diagnosis and follow up of IE is emphasized. Aim The aim was to provide information regarding mortality and adverse events of IE, to determine IE characteristics and to assess current use of imaging in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Similarly, other studies by Njuguna et al ( 3 ) and Noubiap et al ( 12 ) have reported a relatively similar in-hospital mortality due to IE with an in-hospital mortality rate of 22.6% (11.2–31.2%). Surprisingly, the observed mortality is similar to the 20% that is reported in HIC ( 6 , 35 , 36 ). In HIC patients present early and get diagnosed early ( 6 , 36 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, other studies by Njuguna et al ( 3 ) and Noubiap et al ( 12 ) have reported a relatively similar in-hospital mortality due to IE with an in-hospital mortality rate of 22.6% (11.2–31.2%). Surprisingly, the observed mortality is similar to the 20% that is reported in HIC ( 6 , 35 , 36 ). In HIC patients present early and get diagnosed early ( 6 , 36 ).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are similar to what has been reported in previous studies ( 3 , 43 ). On the contrary, Noubiap et al ( 12 ) has reported in their review that Staphylococcus is the leading cause of IE in Africa, same as it is in HIC ( 6 , 36 ). The difference observed between our review and that of Noubiap et al could be due to the difference in the studied populations, we recruited studies across many developing countries and mostly adults while they reviewed African studies with a large proportion of children.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the Euro-Endo registry, TTE has been performed in 91% of cases, while TOE in 53% of native valves' IE [21]. However, some heterogeneity in the diagnostic workup has been reported, with some countries having a more extensive use of imaging, possibly associated with a relatively low mortality [22]. Globally, the data confirm the current role of TTE as a first-line test, while TOE is still limited to selected cases.…”
Section: When To Ask For Transthoracic Echocardiography (Tte) and Whementioning
confidence: 64%
“…Presentation is diverse, varying from patients presenting with isolated fevers and decompensated heart failure to patients presenting with hemorrhagic or ischemic stroke resulting from either septic or thrombus embolization [ 5 ]. Because of its many complications, early diagnosis and treatment of IE are of utmost importance [ 6 ]. We describe a case where delayed recognition of IE resulted in a rare but severe complication culminating in the death of our patient.…”
Section: Introductionmentioning
confidence: 99%